2022
DOI: 10.1186/s40364-022-00381-5
|View full text |Cite
|
Sign up to set email alerts
|

Intratumor microbiome in cancer progression: current developments, challenges and future trends

Abstract: Cancer is a complicated disease attributed to multifactorial changes, which causes difficulties with treatment strategies. Various factors have been regarded as the main contributors, and infectious etiological factors have recently attracted interest. Several microbiomes contribute to carcinogenesis, cancer progression, and modulating cancer treatment by inducing cancerous epithelial cells and chronic inflammation. Most of our knowledge on the role of microbiota in tumor oncogenesis and clinical efficiency is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0
4

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 181 publications
(297 reference statements)
0
25
0
4
Order By: Relevance
“…Neurauter et al found that the higher the FIGO stage of ovarian cancer, the higher the serum L-phenylalanine concentration (45). Xiaoli et al found that the serum L-phenylalanine level in patients with esophageal cancer was signi cantly higher than that in healthy controls, whereas tyrosine levels were signi cantly lower than those in healthy controls (13). Cheng et al found that serum L-phenylalanine concentration in patients with NSCLC was signi cantly elevated (7).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Neurauter et al found that the higher the FIGO stage of ovarian cancer, the higher the serum L-phenylalanine concentration (45). Xiaoli et al found that the serum L-phenylalanine level in patients with esophageal cancer was signi cantly higher than that in healthy controls, whereas tyrosine levels were signi cantly lower than those in healthy controls (13). Cheng et al found that serum L-phenylalanine concentration in patients with NSCLC was signi cantly elevated (7).…”
Section: Discussionmentioning
confidence: 99%
“…Based on this, our goal was to identify predictive biomarkers from peripheral blood through liquid biopsy, which has high sensitivity, cost-effectiveness, and repeatable sampling, and can dynamically re ect the physiological changes of patients after treatment. Currently, common blood biopsy methods in clinical and research studies include exosomes (EVs) (13), tumor-induced platelets (TEP) (14), and microbiota and microbial metabolites (15)(16)(17)(18). However, these methods have disadvantages.…”
Section: Introductionmentioning
confidence: 99%
“…The progression of illnesses such colon cancer metastases, which may affect intestinal lumen homeostasis, is controlled by the disease, dietary behavior patterns, dysbacteriosis of the microbial population, and gastrointestinal endophytic mediators [243][244][245][246][247]. Most models used to decode food, microbiota, and host interactions are animal-based.…”
Section: Discussionmentioning
confidence: 99%
“… 36 Several reviews have compiled detailed tables to clarify the microbial composition of different cancer types. 32 , 37 Due to recent breakthroughs in research of intratumoral microbiota compositions, we have summarized the main bacterial and fungal compositions of eight different cancers published in large-scale cohort studies in recent years (Fig. 2 , Table 1 ).…”
Section: The Characteristics Of Intratumoral Microbiotamentioning
confidence: 99%